Colonic lymphoma presenting acutely with perforated colo-splenic fistula - Al-Zahir, Ali Ahmed (Elsevier, 2012)
INTRODUCTION: Primary colonic lymphoma is rare. It comprises less than 1% of large bowel malignancies. Affected patients often present with non-specific vague symptoms with subsequent delays in diagnosis and management. PRESENTATION OF CASE: An immuno-competent 35-year-old male presented with left iliac fossa pain, fever and constipation. Clinical examination revealed left-sided abdominal peritonism. After the initial radiological and endoscopic investigations, a provisional diagnosis of a localized perforation of a splenic flexure diverticulum was made and ultrasound-guided percutaneous drainage of the abscess was performed. The patient failed to settle on conservative treatment and therefore exploratory laparotomy was carried out. An inflammatory phlegmon consisting of a left paracolic gutter abscess, the spleen and the splenic flexure of the colon was resected en-bloc and a primary colo-colic anastomosis was performed. His operative recovery was complicated by wound infection which was treated conservatively. The histopathology revealed colo-splenic fistula secondary to a perforated colonic non-Hodgkin's lymphoma. The spleen contained multiple metastatic lymphomatous deposits. He was started on chemotherapy and remained well at 5-year follow up. DISCUSSION: Colon non-Hodgkin's lymphoma may present initially with an acute abdomen due to perforation. It mimics any acute surgical condition. Perforation and fistulaization into the spleen is very rare. CONCLUSION: This case highlights the delay and difficulty in diagnosing primary colonic lymphoma without resorting to surgical resection.